Ferulic acid alleviates retinal neovascularization by modulating microglia/macrophage polarization through the ROS/NF-κB axis - Sun, Xiaowei; Ma, Lusheng; Li, Xiao; Wang, Jiao; Li, Yuanbin; Huang, Zijing (Frontiers in Immunology, 2022)
Inflammation plays a pivotal role in ischemia-induced retinal neovascularization. Targeting microglia/macrophage-based neuroinflammation presents a promising therapeutic strategy. Ferulic acid (FA), a natural and active ingredient in plants, exerts favorable anti-oxidative and anti-inflammatory activities. In this study, we investigated the inhibitory effect of FA against hypoxia-induced retinal angiogenesis using cultured retinal vascular endothelial cells and an oxygen-induced retinopathy mouse (OIR) model. The immunoregulatory effect of FA on microglia/macrophage polarization was evaluated by detecting the expression of specific markers for both pro-inflammatory “M1” and anti-inflammatory “M2” phenotypes using co-immunostaining and polymerase chain reaction assays. The underlying molecular mechanism upon FA treatment was also explored. The results showed that FA supplement markedly inhibited retinal pathological angiogenesis both in vivo and in vitro. In addition, FA switched microglia/macrophage polarization from “M1” towards “M2” phenotype and alleviated the inflammatory response. Mechanically, the anti-angiogenic and anti-inflammatory properties of FA were mainly due to blockade of the ROS/NF-κB pathway. Our data demonstrated an anti-angiogenic effect of FA through regulating M1-to-M2 microglia/macrophage polarization, suggesting a potential therapeutic strategy for retinal neovascular diseases.